2004
DOI: 10.1038/sj.cdd.4401483
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apoptosis inhibitor protein Mcl1 linked to neuroprotection in CNS neurons

Abstract: Mcl1 is a Bcl2-related antiapoptotic protein originally isolated from human myeloid leukemia cells. Unlike Bcl2, expression has not been reported in CNS neurons. We isolated Mcl1 in a direct screen for candidate modifier genes of neuronal vulnerability by differential display of mRNAs upregulated following prolonged seizures in two mouse strains with contrasting levels of hippocampal cell death. Mcl1 is widely expressed in neurons, and transcription is rapidly induced in both strains. In resistant C57Bl/6J mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…It has been proposed that the neuroprotective effects of ATF5 are mediated by the transcriptional induction of some proteins with a neuroprotective effect, such as Hsp27, Bcl2 and Mcl1 [58][59][60][61]. Likewise, in our study, we found a significant up-regulation in mcl1, which was also up-regulated in other models of status epilepticus, such as pilocarpine administration in rodents [62].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been proposed that the neuroprotective effects of ATF5 are mediated by the transcriptional induction of some proteins with a neuroprotective effect, such as Hsp27, Bcl2 and Mcl1 [58][59][60][61]. Likewise, in our study, we found a significant up-regulation in mcl1, which was also up-regulated in other models of status epilepticus, such as pilocarpine administration in rodents [62].…”
Section: Discussionsupporting
confidence: 82%
“…At the same time, other genes showed similar changes in gene expression profiles between the two genotypes, including bag3, mcl1, traf2 and bcl10. Interestingly, these genes encode proteins that confer antiapoptotic neuroprotection, which could account for the increase in expression in both WT and lpr mice after KA treatment [62]. Therefore, our results suggest neuroprotective effects in lpr mice after KA administration based on genes that are not activated in this model.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, AUDA-treated SHRSP had only 1 gene up-regulated Ն2-fold and 11 Ն1.5-fold in comparison with WKY ( Figure 5, C and E; and Table 1). Furthermore, AUDA reduced gene expression of 39 apoptotic factors Ն1.5-fold and 32 Ն2-fold versus SHRSP vehicle-treated rats ( Figure 5, B 43 and an antioxidant peroxiredoxin 2 (Prdx2) in the WKY animals (Table 1 and Figure 5E). …”
Section: Apoptosismentioning
confidence: 96%
“…However, Mcl-1 is expressed in cerebellar granule neurons (CGNs) in vivo, 8 and Mcl-1 expression has been associated with neuroprotection in the hippocampus. 9 More recently, elegant studies using different conditional Mcl-1 mouse mutants, showed that Mcl-1 is required for neuronal development, that loss of Mcl-1 sensitizes neurons to DNA damage-induced apoptosis and that Mcl-1 negatively regulates autophagy in starved neurons. 10,11 Therefore, Mcl-1 appears to play a crucial role in neuronal survival.…”
mentioning
confidence: 99%